Penyelesaian Tindak Pidana Pemilu Legislatif oleh Badan Pengawas Pemilu (BAWASLU) Daerah Istimewa Yogyakarta Tahun 2014 - Rani Nurroufah Pratiwi (UIN Sunan Kalijaga Yogyakarta, 2014)
The general election is a manifestation of the people’s softreight in order toproduce a democratic goverment, elections that are direct, general, free, confidential,honest and fair can only be realized if the election management has high integrity andunderstand and respect the civil and political rights of citizens. Weak electionpotentially undermined qualified election organizers have a duty to hold elections byinstitutional national, permanent and independent. One of the importan factors for thesuccess of election it self, the election commission, ellaction watchdog, and honorary boardof election. Superfysory role of the comitte in general election by country or city loworganizing elections, over seeing in the implementation stage of the election in the regencyor city which includes, receving reports of alleged violations of the laws and theimplementation of the election law, and report the findings resolve election disputescontain no element of crime, deliver and report finding to the commition for the countryor city followd up, forward and report finding that are not its responsibility to theotorities to submit a report to the election Supervisory Body Relating to the allegedactions which resulted in disruption of the implementetion stage of elections by electoraladministration in country or city level